Cost Volume Profit Analysis in Procurement of New Machinery as a Basis for Margin Contribution at PT. X in Jakarta - Rizqi, Muhamad Nur; Hurriyaturrohman, Hurriyaturrohman; Mulyana Dali, Rahmat (Jurnal Mahasiswa Akuntansi dan Bisnis (JMAB), 2024)
The purpose of this study is to determine the profit and loss budget of the Printing company "PT. X in 2024 specifically on the new Heidelberg Type CX -104 Brand Printing Machine which is a management decision to increase potential profits as well as profit contribution from overall production activities. This research analyzes cost - volume and profit (CVP) so that it can be known the break-even point of production carried out with the new machine. This research uses Qualitative and quantitative methods using secondary and primary data. In separating semi-variable costs, the regression method is used, namely the cost of electricity and the profit sharing ratio. The results of this study indicate that the profit and loss budget for 2024, especially the use of new machines, experienced a profit in semester 2, as a whole or 1 year the company can get an additional profit of Rp. 206,029,705.90, the acquisition of a contribution margin of Rp1,123,535,357.71. Plate usage varies every month depending on how many plates are used in each production run. The company will start to make a profit on the use of the machine if the plates used in the production carried out exceed 2,720 pieces of plates.